2015
DOI: 10.1097/mat.0000000000000224
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sterilization and Storage Period on Elution of Polyvinylpyrrolidone from Wet-Type Polysulfone Membrane Dialyzers

Abstract: The objectives of this study were to investigate the influence of the sterilization and storage period on elution of polyvinylpyrrolidone (PVP) from wet-type polysulfone (PSu) membrane dialyzers. APS-15SA (APS) dialyzers sterilized by gamma-radiation and RENAK PS-1.6 (RENAK) dialyzers sterilized by autoclaving were compared in this study. Each dialyzer was washed with physiological saline and the amount of PVP eluted from the PSu membrane was measured. Then, experimental use of each dialyzer was performed by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…Gamma sterilization has been discussed to induce crosslinking of PVP with the membrane and to reduce the elution of PVP during treatment as compared to autoclaving. 36 In our present study we found that the gamma sterilized xevonta and ELISIO had a much lower PVP elution than the autoclave steam sterilized Polyflux and THERANOVA. However, the INLINE steam-sterilized FX CorAL and FX CorDiax had the lowest amount of PVP elution across the investigated dialyzers.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Gamma sterilization has been discussed to induce crosslinking of PVP with the membrane and to reduce the elution of PVP during treatment as compared to autoclaving. 36 In our present study we found that the gamma sterilized xevonta and ELISIO had a much lower PVP elution than the autoclave steam sterilized Polyflux and THERANOVA. However, the INLINE steam-sterilized FX CorAL and FX CorDiax had the lowest amount of PVP elution across the investigated dialyzers.…”
Section: Discussionsupporting
confidence: 46%
“…Moreover, PVP stabilization may vary between dialyzers sterilized with different approaches. Gamma sterilization has been discussed to induce cross‐linking of PVP with the membrane and to reduce the elution of PVP during treatment as compared to autoclaving 36 . In our present study we found that the gamma sterilized xevonta and ELISIO had a much lower PVP elution than the autoclave steam sterilized Polyflux and THERANOVA.…”
Section: Discussionsupporting
confidence: 45%
“…However, the APS-11SA dialyzer showed excel-lent blood compatibility compared to the RENAK dialyzer. This is because its PVP (added into the membrane matrix) was insolubilized by cross-linking using gamma rays [127]. Since the RENAK dialyzer was sterilized with an autoclave, an excess amount of PVP could be eluded during the rinsing procedure.…”
Section: Sterilization Processmentioning
confidence: 99%
“…However, the hydrophilic additives, such as PVP, can elute from the membrane matrix due to wall shear stress during ultrafiltration o r as the result of some sterilization techniques [14][15][16][17]. For example, membrane sterilization via autoclaving results in less cross-linked PVP than sterilization via gamma-radiation, which could result in elution of PVP during long-term dialysis therapy [18]. As a consequence, the membrane's structural characteristics and filtration performance would be compromised [14,15,18,19].…”
Section: Membrane Preparationmentioning
confidence: 99%
“…For example, membrane sterilization via autoclaving results in less cross-linked PVP than sterilization via gamma-radiation, which could result in elution of PVP during long-term dialysis therapy [18]. As a consequence, the membrane's structural characteristics and filtration performance would be compromised [14,15,18,19]. Besides, the eluted PVP can be potentially harmful to patients because it can accumulate in internal organs and induce allergies and anaphylactic shock [19][20][21].…”
Section: Membrane Preparationmentioning
confidence: 99%